Penerapan Layanan Informasi Menggunakan Media Audio Visual untuk Meningkatkan Minat Belajar Siswa (Jurnal Wahana Konseling, 2025)
This study aims to increase students' learning interest through the implementation of information services using audio-visual media in class VIII.3 of SMP Negeri 57 Palembang for the 2024/2025 academic year. This research is a Guidance Service Action Research (Penelitian Tindakan Layanan/PTL) conducted in two cycles, involving 30 students as the subjects. Data analysis techniques used include percentage calculations and paired T-Test analysis. The results showed a significant increase in students' learning interest in each cycle. In the pre-test stage, the average score was 90.6 with a percentage of 57% (moderate category). After the intervention in the first cycle, the average increased to 109.4 (68%, high category), and in the second cycle, it further increased to 130.4 (82%, high category). This improvement indicates that information services delivered through audio-visual media have a positive impact on enhancing students' learning interest. Therefore, guidance and counseling services, particularly information services using audio-visual media, can be an effective strategy to foster student interest and active engagement in the learning process.